Atención al cliente en la estación de servicios de combustible y lubricantes para vehículos de motor CLYAN del cantón Baba Parroquia Isla de Bejucal - Vera Franco, Luis Balder (2021)
In this case study covers the problems that exist in the company Clyan, with regard to the poor attention given to the customer, the Clyan Company is a station of fuel services and lubricants for vehicles. Mostly small, large and medium-sized companies aim to satisfy their customers, just as customers with the purchases made generate higher revenues to companies, for this reason each company makes decisions to maximize the efficient quality of customers, since there is competition to attract customers, it is a struggle that these companies that offer fuel and lubricant services live every day , it is important to emphasize that the right attention is sometimes left out because they are more focused on selling the products. In many fuel service stations, it provides a quality of customer service, which is satisfied and returns again for a good service provided, currently this is not the case in the company Clyan, there is a shortfall in the quality of customer service, which affects its commercialization. The work was carried out with the parameters of a qualitative investigation at the Clyan service station, this will support the behavior of the customers of the station, located in the parish of Isla de Bejucal of the canton Baba. The research also conducted a survey, which will determine the problem that Clyan has with the relationship of its customers, and the factors that involve this problem.